Information Source Utilization by Livestock and Poultry Farmers of Uttar Pradesh - Panda, Pratikshya; Tiwari, Rupasi; Handage, Sushant; Dutt, Triveni (Indian Journal of Extension Education, 2021)
The study was conducted during 2020-2021 to assess the information sources utilization pattern of livestock and poultry farmers of Uttar Pradesh. A total of 120 farmers, 40 from each group i.e., dairy, piggery and poultry were selected randomly. Semi-structured personal interview and online survey through google forms were considered together for collection of data keeping in view the COVID-19 second wave. Information source utilization by majority of the respondents was medium. ICT utilization among the respondents was maximum with mean score of 0.63 followed by mass media with mean score of 0.51 and extension agency contact with mean score of 0.498. Education, land holding and experience in farming business were found to be significant contributors in information source utilization. Except age, all the variables such as education, annual income, land holding, experience in farming business and number of trainings undergone were positively correlated with information source utilization of the respondents.